New Product Design: Concept, Measurement, and Consequences - Homburg, Christian; Schwemmle, Martin; Kuehnl, Christina (Journal of Marketing, 2015)
Product design is a source of competitive advantage for companies and is an important driver of company performance. Drawing on an extensive literature review and consumer interviews, the authors define product design and its dimensions. Using data from three samples (6,418 U.S. consumers and 1,083 and 583 European consumers), the authors develop and validate a new scale to measure product design along the dimensions of aesthetics, functionality, and symbolism. In addition, they investigate the impact of these design dimensions on purchase intention, word of mouth, and willingness to pay. The results indicate that the design dimensions positively influence willingness to pay and also have a positive effect on purchase intention and word of mouth, both directly and indirectly through brand attitude.